2001
DOI: 10.1100/tsw.2001.379
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Management: A Tool to Modify Ecosystem Impacts of Nitrogen Deposition?

Abstract: Atmospheric nitrogen deposition has been shown to affect both the structure and the function of heathland ecosystems. Heathlands are semi-natural habitats and, as such, undergo regular management by mowing or burning. Different forms of management remove more or less nutrients from the system, so habitat management has the potential to mitigate some of the effects of atmospheric deposition. Data from a dynamic vegetation model and two field experiments are presented. The first involves nitrogen addition follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 21 publications
6
46
1
Order By: Relevance
“…They are also in the range reported by studies conducted in the British Isles (Kirkham 2001;Power et al 2001) but are somewhat lower than deposition rates in many regions in the Netherlands (Bakema et al 1994;Erisman & de Vries 2000). However, N deposition in the study area exceeded critical load values for dry heathlands (10-20 kg 1.…”
Section:       mentioning
confidence: 40%
See 1 more Smart Citation
“…They are also in the range reported by studies conducted in the British Isles (Kirkham 2001;Power et al 2001) but are somewhat lower than deposition rates in many regions in the Netherlands (Bakema et al 1994;Erisman & de Vries 2000). However, N deposition in the study area exceeded critical load values for dry heathlands (10-20 kg 1.…”
Section:       mentioning
confidence: 40%
“…These differences are mainly related to the impact of the temperature of the fire, which strongly affects the amount of burned organic matter in the above-ground biomass and the organic layer (Forgeard & Frenot 1996;Power et al 2001). In addition, nutrient loss increases with increasing organic matter available for combustion (Diemont 1996).…”
Section:    -   mentioning
confidence: 99%
“…Habitat management practices (e.g., from harvesting/mowing) decreasing ecosystem N stocks and mitigating the effects of N additions have also been found in grassland or heathland ecosystems (Willems, 2001;Power et al, 2001;Barker et al, 2004). Barker et al (2004) suggested that intensive mowing treatments in heathlands could result in a shift in balance between competing species by decreasing the response of the originally dominated species to N deposition.…”
Section: Discussionmentioning
confidence: 98%
“…Typically, in heathland vegetation sod cutting and removal of the top soil layer is used as an effective measure to remove nitrogen (e.g., Britton and Fisher, 2007;Power et al, 2001;Terry et al, 2004). In aquatic environments, like water bodies, dredging is applied to remove large quantities of accumulated nitrogen.…”
Section: Figure 22 the Spatial Distribution Of Tsum Values Tsum <25mentioning
confidence: 99%